A modular approach to the bisbenzylisoquinoline alkaloids tetrandrine and isotetrandrine. Issue 16 (24th February 2020) - Schütz, Ramona; Meixner, Maximilian; Antes, Iris; Bracher, Franz
Abstract : A modular short-step synthesis of the bisbenzylisoquinoline alkaloids tetrandrine and isotetrandrine was developed employing N -acyl-Pictet–Spengler reaction and Ullman diaryl ether synthesis as central steps. Abstract : An efficient racemic total synthesis of the bisbenzylisoquinoline alkaloids tetrandrine and isotetrandrine in four different routes is reported herein. Key steps of the synthesis include N -acyl Pictet–Spengler condensations to access the tetrahydroisoquinoline moieties, as well as copper-catalyzed Ullmann couplings for diaryl ether formation. Starting from commercially available building blocks tetrandrine and isotetrandrine are accessed in 12 steps. Depending on the sequence of the four central condensation steps, equimolar mixtures of both diastereomers or predominantly tetrandrine or its diastereomer isotetrandrine are obtained. Through computational analysis we were able to rationalize the differences in the observed diastereomeric specificities.